Transformação digital como fator de influência na gestão do conhecimento de servidores públicos atuantes no teletrabalho - Andrade, Michely Uany Santana de (2024)
Objective: This study aims to verify the influence of digital transformation on the knowledge management of employees who work remotely at the Federal Institute of Bahia (FIBA). Methodology: Characterized as a single case study in a federal educational institution, this research adopts a quantitative approach, using Principal Component Analysis (PCA) and Simple Linear Regression. This descriptive and exploratory method aims to identify and quantify the relationships between digital transformation and knowledge management, providing a solid empirical basis for the study's conclusions. Main Results: The results indicate that digital transformation has a significant influence on knowledge management. Digital transformation contributes to the improvement of internal processes and increases the efficiency of tasks performed by employees. In addition, knowledge management proves to be essential for the success of digital transformation and should be treated as a strategic priority. The study analyzed 47 DT and KM variables that, after applying PCA, were reduced to 42, grouped into 2 main components C1(KM) and C2(DT), resulting, after applying linear regression, in a strong influence of the DT variable on KM in telework environments, with emphasis on the variables DT17, DT8, DT16, DT21, DT10 and DT19 that most significantly affected KM. Relevance and Originality: This study offers contributions by exploring the adaptation of public administration to the digital environment, focusing on knowledge management as a strategic resource. The research highlights the perspective of telework employees, identifying knowledge gaps and suggesting the need for public policies that keep pace with the digital transformation. This is an original contribution to the debate on the modernization of public administration. Theoretical, Methodological, and Management Contributions: The application of PCA and Simple Linear Regression validated the hypotheses that digital transformation and knowledge management are interrelated, with the former intensifying the latter, and knowledge management, in turn, enhancing the effects of digital transformation. Methodologically, the study offers a replicable model for future research in the field of digital public management. Social and Management Contributions: Understanding the impact of digitalization on the knowledge management of teleworking civil servants can guide the formulation of more inclusive and efficient policies, promoting digital inclusion and supporting the implementation of teleworking in public administration. The study findings also suggest strategies to improve the working conditions and productivity of civil servants in digital environments, and can be applied to other spheres of public administration seeking to adapt to teleworking, contributing to the advancement of knowledge and academic debate in the area.